Competition Entry and Relative Performance Feedback: The Importance of Information Disaggregated by Gender - Sabrina Jeworrek (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
By providing different forms of performance feedback before choosing between a piece-rate and a tournament compensation scheme, I test whether the gender tournament gap diminishes in size since individuals' entry decision might be driven by incorrect self-assessments. Only the provision of information on average performance by gender indeed shrinks the gender tournament gap, which is especially due to men with below average ability opting for the piece-rate more often. These results highlight that beliefs on one's own and others' abilities are still biased by gender stereotypes.
Keywords: C91; D82; J16; 330